First mile access networks and enabling technologies - Gumaste, Ashwin (Cisco Press networking technology series., 2004)
Learn about the technologies that drive fast broadband access in the first mile and master the design of first mile access networks Understand the motivating forces behind first mile access networks and learn about the technology and business requirements for first mile access solutions Master the design of passive optical networks (PON) Build EPON solutions and differentiate them from BPON and GPON Enhance bandwidth capacity in the access area using CWDM technology Learn about and design DSL and power-line communication (PLC) networks Discover the use of WiFi in the first mile and study the subsystems involved in a WiFi solution Learn the importance of management in first mile access networks and create a business case for diverse first mile access networks First Mile Access Networks and Enabling Technologies provides a platform for showcasing first mile access technologies and associated network solutions. Using this book, you learn about the bandwidth bottleneck within the first mile and explore the resulting business prospects. Benefit from a thorough and thoughtful discussion of the business case for the first mile, which helps you approach the issue from multiple perspectives. Examine multiple access technologies, understand the diversity of solutions within this area, and take your solutions further using sound and unique management techniques. Utilize the solid and tested implementation method provided by this book to remove networking anomalies, such as the digital divide. This book helps you understand and capitalize on the market opportunity presented by the first mile. First Mile Access Networks and Enabling Technologies covers multiple technologies, protocols, and business methods and can be used to understand the growth of first mile access networks and resulting business opportunities. This book is part of the Networking Technology Series from Cisco Press, which offers networking professionals valuable information for constructing efficient networks, understanding new technologies, and building successful careers.